2019
DOI: 10.1080/21645515.2018.1564432
|View full text |Cite
|
Sign up to set email alerts
|

Perception and knowledge of HPV-related and vaccine-related conditions among a large cohort of university students in Italy

Abstract: HPV is involved in cervical, anal, penile, vulvar and oropharyngeal cancers, as well as genital warts. It is important to investigate knowledge and attitudes among university students, considering in this age a shift in healthcare decision-making from parents to students themselves. The aim of this study was to estimate knowledge and perception of HPV in terms of potential shame for HPV-related conditions, trust in vaccine efficacy and worry for potential side effects. The study involved students (18-25 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
7
0
3
Order By: Relevance
“…These results could support Public Health policymakers in implementing multicomponent interventions including organizational and educational strategies, which warrant a comprehensive approach to improve HPV vaccine compliance [ 24 , 87 ].…”
Section: Discussionmentioning
confidence: 96%
“…These results could support Public Health policymakers in implementing multicomponent interventions including organizational and educational strategies, which warrant a comprehensive approach to improve HPV vaccine compliance [ 24 , 87 ].…”
Section: Discussionmentioning
confidence: 96%
“…Strategies aimed at increasing vaccination coverage are varied. Evidence showed that a number of different intervention strategies have been taken into account, as for instance, educational interventions aimed at improving awareness and perception of both the disease and the vaccine availability [ 20 , 21 ], health literacy interventions [ 22 ], facilitation of healthcare access and delivery [ 23 , 24 ] and as a last resort whenever needed, the establishment of compulsory vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…36 Other papers address provider, parent, and patient issues specific to understudied countries, such as China, India, and Italy, as well as areas of vaccine hesitancy and/or low vaccination uptake in the U.S. and Canada. [37][38][39][40][41][42][43][44] Another research report found that few providers in a U.S. regional health plan administered vaccine in a way that was consistent with Healthcare Effectiveness Data and Information Set benchmarks. 45 Two articles explore issues of trust among African American parents and how this impacts vaccination.…”
Section: Hpv Vaccination Policymentioning
confidence: 96%